The impact of Covid-19 healthcare emergency on the psychological well-being of health professionals: a review of literature - Della Monica, A.; Ferrara, P.; Dal Mas, F.; Cobianchi, L.; Scannapieco, F.; Ruta, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. The Coronavirus pandemic (Covid-19) was first identified in December 2019 in the city of Wuhan, China, and later caused a severe health crisis, causing massive disruptions to most healthcare systems worldwide. The Covid-19 health emergency has seen healthcare workers in the front line facing all the difficulties related to the care burden. One of the most significant and probably underinvestigated aspects is the psychological stress of the healthcare staff managing the emergency. The aim of the paper is to analyze the literature on the impact of the Covid-19 crisis on the psychological well-being of health professionals. Methodology. We conducted a systematic review of articles published on this topic during the months from January 2020 to December 2020, searching on Pub Med, Scopus and Web of Science databases. Results. Most of the issues can be summarized into five conceptual categories: Stress, Depression and Infection Anxiety, Anguish, Insomnia, Post Traumatic Stress Disorder, and Suicide. The literature identifies many factors contributing to the onset of anxiety, depression, and stress, like the fear of contracting the disease and transmitting it to family members and friends, stressful shifts, and little rest among several others. The literature highlights the needs for adequate measures, including proper psychological support. Conclusion. The conducted review suggests that the behaviours of healthcare professionals during the emergency phase of the Covid-19 pandemic show psychological disorders that can compromise mental health. Therefore, there is a call for those in chief like hospital managers and policymakers to take action, promoting measures like surveillance, monitoring, and psychological support among others, to increase the resilience of healthcare workers, limiting stress and anxiety and allowing them to keep their performance at work.